Political Budget Cycles, Retrospective Voting, and Candidate Strength in Indonesian Local Elections - Riya Dwi Handaka; Tri Widyastuti; Apollo Daito (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
This study examines the structural relationships among fiscal strategy, intergovernmental transfers, financial accountability, economic development performance, candidate strength, and incumbent electoral performance in local elections. The study uses secondary data from 214 Indonesian regencies and municipalities where incumbent regional heads or deputy heads ran again in the 2020 simultaneous local elections. Fiscal indicators are measured using realized local budget data and audit results from the 2019 local government budget, representing the pre-election period, while electoral performance is measured using election results and incumbent vote share. The data are analyzed using Structural Equation Modeling–Partial Least Squares. The findings show that candidate strength has the strongest structural relationship with incumbent electoral performance in the specified model. Among the fiscal strategies examined, only the revenue strategy shows positive structural relationships with both economic development performance and incumbent electoral performance. Expenditure strategy and intergovernmental transfers are negatively associated with economic development performance and do not show direct structural relationships with incumbent electoral performance. Financing strategy is not significantly related to either development or electoral performance. Financial accountability shows a positive structural relationship with economic development performance, but not with incumbent electoral performance. The mediation test indicates that economic development performance does not mediate the structural relationships between fiscal strategy, intergovernmental transfers, financial accountability, and incumbent electoral performance. These findings suggest that, in the specified model, incumbent electoral performance is more closely associated with candidate strength and local revenue capacity than with economic development performance as a retrospective voting mechanism.